Exercise dependence among marathon runners in relation to their demographic and training status - Starzak, Joanna; Sas-Nowosielski, Krzysztof; Pajerska, Katarzyna (Journal of Education, Health and Sport, 2019)
Introduction and purpose. Taking into account that endurance athletes might be at an increased risk for exercise dependence there is a need for monitoring the prevalence and correlates of this phenomenon in them. The aim of the study was assessing the prevalence of exercise addiction among marathon runners and identify its socio-demographic and training correlates. Material and method. A total of 132 runners ranging in age from 18–69 years old took part in the study. To assess the exercise dependence a polish version of the Exercise Dependence Scale-21 was used. Results. The results suggest that being at risk for exercise dependence concerns 12% of runners and – except of withdrawal factor - is not related to sex but is related to age. No significant differences were found between training volume groups and exercise dependence. Conclusions. More than one on ten marathoners seem to be addicted to running suggesting the need to increase knowledge on this phenomenon in this community.